Effectiveness of 70% Ethanol Extract of Pomegranate (Punica granatum Linn) Against the Healing Process of Incisions and Burns in Mice - Meilina Ratna Dianti; Siti Maimunah (Sanata Dharma University, 2025)
A wound is a traumatic occurrence that damages the skin's and subcutaneous tissue's continuity. For the treatment of skin wounds, it is normal practice in the medical community to administer analgesics, anti-inflammatories, antibiotics, and antiseptics. Anti-inflammatory, antibacterial, and antioxidant properties are required, as well as assistance for cell proliferation in the production of protein and collagen for the regeneration process. Pomegranate is frequently used as herbal medicine and is thought to heal various diseases and ailments, including burns. This investigation will assess the effects of 70% ethanol extract from pomegranate fruit on mouse incisions and second-degree burns. To assess the effect of the extract on the healing of cuts and burns in mice, wounds and second-degree burns were made and treated with a 70% ethanol extract of pomegranate at doses of 7%, 14%, and 28%. Administration of pomegranate fruit extract in 70% ethanol at the optimum dose of 28% was shown to considerably boost wound healing activity and this finding demonstrates the ability of pomegranate extract to treat wounds.